Simulación CFD para determinar el potencial del recurso eólico en Valledupar, Colombia (2025)
This thesis focuses on evaluating the potential of wind energy in the city of Valledupar, Colombia, using wind speed as the main parameter. To do so, the OpenFOAM-v2406 software is used, which allows for detailed simulations of wind behavior in the region. The project methodology combines data from available wind maps and atlases, together with computational fluid dynamics (CFD) studies. This allows for simulating wind behavior at meso and micro scales, providing more accurate information on the local wind resource. By reducing the scale of the data, the study seeks to offer a more faithful representation of wind conditions in Valledupar, overcoming the limitations of global data that are often interpolated and do not adequately reflect local characteristics.